2008
DOI: 10.1042/bst0360950
|View full text |Cite
|
Sign up to set email alerts
|

The long-chain fatty acid receptor, GPR40, and glucolipotoxicity: investigations using GPR40-knockout mice

Abstract: GPR40 (G-protein-coupled receptor 40) has been shown to be a physiologically relevant receptor for long-chain fatty acids. It is a family A G-protein-coupled receptor highly expressed in the beta-cell where it increases insulin secretion by signalling via Gq and phospholipase C. Fatty acids are well known to mediate both acute stimulatory effects and chronic detrimental effects on the beta-cell. GPR40-transgenic and GPR40-/- animals have been important tools in studies of the metabolic effects of GPR40. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…Brownlie et al have also examined this topic in a further group of GPR40 KO mice and, consistent with all other reports, they observed that loss of the receptor leads to impaired insulin secretory responses to fatty acids [69]. They also confirmed that deletion of GPR40 failed to prevent hepatic steatosis during high fat feeding.…”
Section: Role Of Gpr40 In Lipotoxicitysupporting
confidence: 64%
“…Brownlie et al have also examined this topic in a further group of GPR40 KO mice and, consistent with all other reports, they observed that loss of the receptor leads to impaired insulin secretory responses to fatty acids [69]. They also confirmed that deletion of GPR40 failed to prevent hepatic steatosis during high fat feeding.…”
Section: Role Of Gpr40 In Lipotoxicitysupporting
confidence: 64%
“…The druggability of GPCRs in general, the relative selectivity of GPR40 production in beta cells, and the 'incretin-like' effects of long-chain fatty acids, which only stimulate insulin secretion when glucose levels are elevated, all favour the development of GPR40 agonists to enhance insulin secretion in type 2 diabetes without the risk of hypoglycaemia [4,5]. However, because prolonged exposure to elevated levels of fatty acids is detrimental to beta cell function [33], the possibility that chronic stimulation of GPR40 might be deleterious led some groups to propose that GPR40 antagonists-rather than agonists-should be designed for therapeutic purposes [34,35]. Thus, Steneberg et al [35] reported that Gpr40 −/− mice are protected from high-fat-diet-induced insulin resistance and glucose intolerance and that transgenic overexpression of GPR40 in beta cells impairs insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule GPR40 agonists derived from thiazolidinedione compounds were shown to potentiate glucose-stimulated insulin release and reduce blood glucose in normal mice (Tan et al, 2008) while a smallmolecule GPR40 antagonist (ANT 203) blocked the acute amplifying effects of palmitate on glucose-stimulated insulin release in mouse islets (Brownlie et al, 2008 . Moreover, the long-term iNOS-stimulating detrimental effect of palmitate on glucose-induced insulin release after culture of mouse islets was efficiently counteracted at the GPR40 level in the presence of rosiglitazone .…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to long-term effects two well recognized studies using genetic ablation of GPR40 in mice have given very controversial results showing on the one hand that such animals were as sensitive as controls to long-term deleterious effects by FFA (Latour et al, 2007) and on the other hand , in contrast, that deletion of GPR40 protected the islets from FFA-induced dysfunction as well as from obesityinduced hyperinsulinaemia (Steneberg et al, 2005). Moreover, most data from several subsequent studies using mice with GPR40 deletion or overexpression suggested that loss of GPR40 did not protect against the deleterious effects of long-term exposure of the islets to elevated FFA or high fat feeding but instead that GPR40 activation could lead to facilitation of glucose-induced insulin secretion ,Brownlie et al, 2008,Nagasumi et al, 2009,Tan et al, 2008. The marked discrepancies between these studies are difficult to explain but different techniques including unwanted side effects of GPR40 deletion and overexpression are likely involved.…”
Section: Introductionmentioning
confidence: 99%